Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our Q&A platform and get accurate answers to all your questions from professionals across multiple disciplines. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
Answer:
1. X^2+1/2x = [tex]x(x+\frac{1}{2})[/tex]
2. X^2+2x-3 = [tex](x-1)(x+3)[/tex]
3. (2x-3)^2 = (2x-3)(2x-3)
4. X^3+2x^2-19x-20 = [tex](x+1)(x-4)(x+5)[/tex]
Step-by-step explanation:
Each expression can be written as a product of linear factors as follows
1. X^2+1/2x ⇒ [tex]x^{2} + \frac{1}{2}x[/tex]
[tex]x^{2} + \frac{1}{2}x[/tex] = [tex]x(x+\frac{1}{2})[/tex]
Hence, X^2+1/2x = [tex]x(x+\frac{1}{2})[/tex]
2. X^2+2x-3 ⇒ [tex]x^{2} +2x-3[/tex]
[tex]x^{2} +2x-3 = x^{2} +3x-x-3[/tex]
[tex]x^{2} +3x-x-3 = x(x+3) -1(x+3)[/tex]
[tex]x(x+3) -1(x+3) = (x-1)(x+3)[/tex]
Hence, X^2+2x-3 = [tex](x-1)(x+3)[/tex]
3. (2x-3)^2 ⇒[tex](2x-3)^{2}[/tex]
[tex](2x-3)^{2} = (2x-3)(2x-3)[/tex]
Hence, (2x-3)^2 = (2x-3)(2x-3)
4. X^3+2x^2-19x-20 ⇒ [tex]x^{3}+2x^{2} -19x -20[/tex]
[tex]x^{3}+2x^{2} -19x -20 = (x+1)(x^{2} +x-20)[/tex]
First,
[tex]x^{2} +x-20 = x^{2} +5x-4x-20\\x^{2} +5x-4x-20= x(x+5)-4(x+5)\\x(x+5)-4(x+5) = (x-4)(x+5)[/tex]
∴ [tex](x+1)(x^{2} +x-20) = (x+1)(x-4)(x+5)[/tex]
Hence, X^3+2x^2-19x-20 = [tex](x+1)(x-4)(x+5)[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.